Silver-coated copper powder and preparation method thereof

The copper powder is activated by acid-base solution and combined with the replacement reaction and redox reaction, a dense silver layer is formed, which solves the problems of poor density and weak binding strength of the silver layer of silver coated copper powder in the prior art, and reduces costs and improves reliability effect.

CN119387586APending Publication Date: 2025-02-07NORTHWEST UNIV
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411695960.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the silver layer of silver-clad copper powder has poor density and weak bonding force between the silver layer and the copper core, resulting in high production cost and insufficient application reliability.

Method used

The copper powder is surface activated by acid-base solution, and a dense and highly active elemental silver layer is formed through replacement reaction and redox reaction, and treated with a coating agent to improve the density and binding strength of the silver-clad copper powder.

Benefits of technology

The silver layer distribution of silver coated copper powder is achieved, and the copper-silver bonding force is better, which reduces the metallization cost and improves the product's density and application reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387586A_ABST
    Figure CN119387586A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cell materials, and particularly relates to silver-coated copper powder and a preparation method thereof. A preparation method of silver-coated copper powder comprises the following steps that copper powder subjected to surface activation through an acid-base solution and a complexing agent are dissolved in water, and copper powder turbid liquid is obtained; dropwise adding a silver source solution into the copper powder turbid liquid to carry out a replacement reaction, and adjusting the pH value of the solution after the reaction to obtain a silver-coated copper powder precursor turbid liquid; and dropwise adding a reducing agent solution into the silver-coated copper powder precursor turbid liquid, then dropwise adding a silver source solution, carrying out oxidation-reduction reaction, carrying out solid-liquid separation, washing, and drying to obtain the silver-coated copper powder. According to the preparation method provided by the invention, in the chemical oxidation reduction process, the silver-coated copper powder with different silver layer distribution structures, compact silver coating structure and better performance is obtained by regulating and controlling the dropping sequence and dropping rate of the reducing agent solution and the silver source solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cell materials, and in particular relates to silver-coated copper powder and a preparation method thereof. Background Art

[0002] The utilization rate of emitter passivation and back contact (PERC) cells has reached its limit, and tunnel oxide passivation contact (TOPCon) cells still have some market potential due to the transformation and upgrading of laser induced sintering technology. In contrast, the intrinsic amorphous layer heterojunction (HJT) cells have the advantages of simple process, excellent passivation performance, weak late attenuation, and can be combined with stacked cells, which are greatly favored by the market. In addition, the conversion efficiency of the back contact crystalline silicon heterojunction solar cell independently developed by Longi Green Energy has set a world record of 27.09%. According to the latest China Photovoltaic Industry Development Roadmap (CPIA, 2023-2024), HJT cells are expected to occupy about 30% of the market share by 2030. One of the biggest challenges hindering the industrialization of HJT cells is the high metallization cost due to the low-temperature process of double-sided silver consumption and smaller grid spacing.

[0003] In order to further reduce the metallization cost, using base metals instead of silver has become a practical solution. Among them, silver-coated copper powder, which combines the advantages of Ag and Cu, has the potential to reduce electrode costs by 30-50%, showing a significant cost reduction effect. In addition, it is expected that silver-coated copper electrodes will occupy more than 70% of the front metal electrode technology market by 2030.

[0004] At present, in the prior art, the surface coating of copper powder with silver often adopts the technology of replacement reaction method, spray pyrolysis method, chemical reduction method, and replacement and chemical deposition composite method. Among them, the replacement and chemical deposition composite method is to first use the reducing property of copper to coat a part of the silver particles on the surface, and then add a reducing agent. However, during the replacement reaction of copper and silver, copper ions will generate copper hydroxide precipitates. These precipitates will adhere to the surface of copper powder, hindering the continued deposition of silver plating, making the silver plating on the surface of the obtained silver-coated copper powder loose. In general, the cost of this type of method is relatively high, and the prepared silver-coated copper powder has relatively poor density and bonding, resulting in insufficient application reliability. Summary of the invention

[0005] In order to solve the above-mentioned technical problems existing in the prior art, the present invention provides a silver-coated copper powder and a preparation method thereof, so as to overcome the technical problems of poor density of the silver layer of the silver-coated copper powder in the prior art in constructing different structural methods and weak bonding force between the silver layer and the copper core.

[0006] In order to achieve the above object, in the first aspect, a method for preparing silver-coated copper powder adopts the following technical scheme: A method for preparing silver-coated copper powder comprises the following steps: Dissolving the copper powder surface-activated by the acid-base solution and the complexing agent in water to obtain a copper powder suspension; Adding a silver source solution dropwise to the copper powder suspension to carry out a replacement reaction, and adjusting the pH of the solution after the reaction to obtain a silver-coated copper powder precursor suspension; A reducing agent solution is firstly added dropwise to the silver-coated copper powder precursor suspension, and then a silver source solution is added dropwise to carry out an oxidation-reduction reaction, and then the solid-liquid separation, washing and drying are performed to obtain the silver-coated copper powder.

[0007] Furthermore, the method also includes the steps of: coating the silver-coated copper powder with a coating agent, solid-liquid separation, washing, and drying.

[0008] Further, the acid-base solution includes an acidic solution and an alkaline solution; The acidic solution includes one or more of HCl solution, HNO3 solution, H2SO4 solution, and H2O2 solution, and the concentration of the acidic solution is 5 wt% to 20 wt%; The alkaline solution includes one or more of NaOH solution, Na2CO3 solution, and Na3PO4 solution, and the concentration of the alkaline solution is 5 wt%~20 wt%.

[0009] Furthermore, the complexing agent includes one or more of ethylenediaminetetraacetic acid, tartaric acid, and citric acid; the mass ratio of the complexing agent to the copper powder is (0.5-1.5):1.

[0010] Further, the silver source solution includes one of AgNO3, a mixture of AgNO3 and gum arabic, and a mixture of AgNO3 and gelatin; The reducing agent solution is C6H8O6 solution, FeSO4 solution, C6H 12 O6 solution or more.

[0011] Furthermore, the concentration of AgNO3 in the silver source solution is 0.3 M to 0.8 M, and the mass ratio of gum arabic or gelatin to AgNO3 is (0.02 to 0.1):1; The reducing agent solution has a concentration of 0.3 M to 0.8 M.

[0012] Furthermore, in the replacement reaction step, the reaction temperature is 40°C~70°C, the mass ratio of the added amount of AgNO3 to the copper powder is (0.02~0.35):1, the dropping rate of the silver source solution is 1 mL / min~10 mL / min, the stirring rate is 200 rpm~600 rpm, the reaction time is 5 min~15 min, and the pH of the solution is adjusted to <1.5 after the reaction.

[0013] Furthermore, in the oxidation-reduction reaction step, the molar ratio of the amount of reducing agent added to AgNO3 is (0.5~1.5):1; the droplet acceleration rate of the reducing agent solution is 1 mL / min~20 mL / min; the mass ratio of the amount of AgNO3 added to the copper powder is (0.08~1.30):1, the droplet acceleration rate of the silver source solution is 1 mL / min~20 mL / min, the stirring rate is 200 rpm~600 rpm, the reaction time is 25 min~35 min, and after solid-liquid separation, washing is performed until the conductivity of the cleaning liquid is <15 μS / cm.

[0014] Further, the coating agent includes one or more of ethylamine, stearic acid, palmitic acid, oleic acid, linoleic acid, and ricinoleic acid; The mass ratio of the coating agent to the silver-coated copper powder is (0.005-0.01):1, the coating temperature is 20°C-30°C, and the stirring rate is 200 rpm-600 rpm.

[0015] In the second aspect, a silver-coated copper powder adopts the following technical solution: A silver-coated copper powder is prepared by using any of the above-mentioned methods for preparing the silver-coated copper powder.

[0016] Beneficial effects of the present invention: The invention provides a method for preparing a silver-coated copper powder. The reduction potential of copper is lower than that of silver. Copper directly undergoes a replacement reaction with a silver source to form a dense and highly active single silver layer on the surface of a copper matrix, which is equivalent to a sensitization process. Then, a reducing agent and an oxidizing agent are added, and the silver particles continue to grow on the replaced silver particles, and finally a silver-coated copper powder with uniform distribution of the silver layer and better copper-silver bonding force is formed. In the chemical oxidation-reduction process, by regulating the drop order and drop rate of the reducing agent solution and the silver source solution, a silver-coated copper powder with different silver layer distribution structures, a compact silver plating structure and better performance is obtained.

[0017] The present invention also provides a silver-coated copper powder, wherein the silver content of the silver-coated copper powder is 20%. 50 The diameter is 1~3 μm, and the tap density is 3.5~5.5 g / cm 3 The initial oxidation temperature is 230~300℃, and the body resistivity of the silver-coated copper paste is 14×10 -6 ~80×10 -6 Ω·cm. At a lower silver content, it has excellent electrochemical performance and a higher initial oxidation temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of the silver-coated copper powder prepared in Example 4; Figure 2 Thermogravimetric diagram of the silver-coated copper powder prepared in Example 4; Figure 3 This is the XRD pattern of the silver-coated copper powder prepared in Example 4. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present application will be further described in detail below in conjunction with the accompanying drawings. The described embodiments should not be regarded as limiting the present invention. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0020] In the following description, reference is made to "some embodiments", which describe a subset of all possible embodiments, but it is understood that "some embodiments" may be the same subset or different subsets of all possible embodiments, and may be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present invention have the same meaning as those commonly understood by those skilled in the art to which the embodiments of the present invention pertain. The terms used in the embodiments of the present invention are only for the purpose of describing the embodiments of the present invention and are not intended to limit the present invention.

[0021] Those skilled in the art should understand that in the following description of the embodiments of the present invention, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0022] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "an" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0023] It will be appreciated by those skilled in the art that the numerical ranges in the embodiments of the present invention are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values ​​in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.

[0024] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the art. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test cases of the present invention. All documents mentioned in this specification are generally incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this application shall prevail.

[0025] It should be noted that all raw materials and / or reagents in the examples of the present invention are purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0026] The instrument information used in the present invention is as follows: The electronic balance is a ME104E electronic balance produced by Mettler-Toledo Instrument Co., Ltd., and the magnetic heating stirrer is an IKA RCT magnetic heating stirrer produced by (IKA Guangzhou) Instrument Equipment Co., Ltd. basic magnetic heating stirrer, tabletop high-speed centrifuge model TG16-WS produced by Hunan Xiangyi Laboratory Instrument Development Co., Ltd., ultrasonic cleaner model KQ5200 produced by Kunshan Ultrasonic Instrument Co., Ltd., vacuum drying oven model DZK-6250 produced by Shanghai Yiheng Scientific Instrument Co., Ltd., laser particle size analyzer model BT-9300ST produced by Dandong Baxter Instrument Co., Ltd., scanning electron microscope model SU8010 produced by HITACHI, and X-ray energy dispersive spectrometer (EDS) was used to analyze the elemental composition of the samples, differential scanning calorimeter model SDTQ600 produced by TA Company of the United States, X-ray powder diffractometer model D8 ADVANCE produced by Bruker Analytical Instruments of Germany.

[0027] The reagent information used in the present invention is as follows: Silver nitrate, molecular formula is AgNO3, reagent purity is AR ≥ 99.8%, manufacturer is Tianjin Damao Chemical Reagent Factory; ethylenediaminetetraacetic acid (EDTA), molecular formula is C 10 H 16 N2O8, reagent purity is AR ≥ 99%, the manufacturer is McLean Biochemical Technology Co., Ltd.; EDTA-2Na, molecular formula is C 10 H 14N2Na2O8, reagent purity is AR ≥ 99%, the manufacturer is McLean Biochemical Technology Co., Ltd.; sodium hydroxide, molecular formula is NaOH, reagent purity is AR ≥ 95%, the manufacturer is Tianjin Tianli Chemical Reagent Co., Ltd.; sodium carbonate, molecular formula is Na2CO3, reagent purity is AR ≥ 99.5%, the manufacturer is Tianjin Tianli Chemical Reagent Co., Ltd.; ethylene glycol (EG), molecular formula is (CH2OH)2, reagent purity is AR ≥ 98.5%, the manufacturer is Tianjin Damao Chemical Reagent Factory; anhydrous ethanol, molecular formula is C2H5OH, reagent purity is AR ≥ 99.7%, the manufacturer is Tianjin Damao Chemical Reagent Factory; ascorbic acid, molecular formula is C6H8O6, reagent purity is AR ≥ 99%, the manufacturer is Xilong Science and Technology Co., Ltd.; glucose, molecular formula is C6H 12 O6, reagent purity is AR ≥ 99.5%, the manufacturer is McLean Biochemical Technology Co., Ltd.; hydroquinone, molecular formula is C6H6O2, reagent purity is AR ≥ 99%, the manufacturer is McLean Biochemical Technology Co., Ltd.

[0028] The technical method of the present invention will be further described below in conjunction with specific embodiments.

[0029] This embodiment provides a method for preparing silver-coated copper powder, comprising the following steps: Dissolving the copper powder surface-activated by the acid-base solution and the complexing agent in water to obtain a copper powder suspension; Adding a silver source solution dropwise to the copper powder suspension to carry out a replacement reaction, and adjusting the pH of the solution to obtain a silver-coated copper powder precursor suspension; A reducing agent solution is firstly added dropwise to the silver-coated copper powder precursor suspension, and then a silver source solution is added dropwise to carry out an oxidation-reduction reaction, and then the solid-liquid separation, washing and drying are performed to obtain the silver-coated copper powder.

[0030] The average particle size of the copper powder has a wide selection range. Preferably, the average particle size of the copper powder is 0.3 μm~10 μm, and more preferably 1 μm~3 μm. The copper powder is cleaned in advance, alternately dissolved in pre-made anhydrous ethanol and deionized water, and ultrasonically cleaned. The number of alternating cleanings is 2~4 times, and the ultrasonic cleaning time is 5 min~10 min.

[0031] In some embodiments, the method further includes the steps of coating the silver-coated copper powder with a coating agent, solid-liquid separation, washing, and drying.

[0032] In some embodiments, the acid-base solution includes an acidic solution and an alkaline solution; the acidic solution includes one or more of HCl solution, HNO3 solution, H2SO4 solution, and H2O2 solution, and the concentration of the acidic solution is 5 wt% to 20 wt%; The alkaline solution includes one or more of NaOH solution, Na2CO3 solution, and Na3PO4 solution, and the concentration of the alkaline solution is 5 wt%~20 wt%.

[0033] The surface activation treatment temperature of the copper powder is room temperature (25±3℃); the copper powder is dissolved in an alkaline solution, ultrasonically stirred, and centrifuged. The ultrasonic cleaning time is 5 min~10 min, the centrifugal speed is 500 rpm~1000 rpm, and the number of centrifugation is 3~6 times; the copper powder is dissolved in an acidic solution, ultrasonically stirred, and centrifuged. The ultrasonic cleaning time is 5 min~10 min, the centrifugal speed is 500 rpm~1000 rpm, and the number of centrifugation is 3~6 times.

[0034] In some embodiments, the complexing agent includes one or more of ethylenediaminetetraacetic acid, tartaric acid, and citric acid; the mass ratio of the complexing agent to the copper powder is (0.5-1.5):1.

[0035] The addition of the complexing agent can make the copper powder form a stable suspension, avoid the accumulation and agglomeration of the copper powder, accelerate the reaction rate of the replacement reaction, and form a layer of elemental silver on the surface of the copper powder.

[0036] In some embodiments, the silver source solution includes one of AgNO3, a mixture of AgNO3 and gum arabic, and a mixture of AgNO3 and gelatin; the reducing agent solution is C6H8O6 solution, FeSO4 solution, C6H 12 O6 solution or more.

[0037] The silver source can be a soluble salt of silver as the Ag in the replacement reaction. + The silver source is preferably AgNO3. Meanwhile, a mixed solution of AgNO3 and a dispersant can also be used as the silver source solution. Preferably, gum arabic or gelatin is used as a dispersant to improve the dispersibility of the silver-coated copper powder, thereby improving the tap density of the silver-coated copper powder.

[0038] The reducing agent is ascorbic acid, ferrous salt and glucose, preferably ascorbic acid; the reducing agent and Ag + A redox reaction occurs, and the silver element grows on the surface of the silver-plated layer on the surface of the silver-coated copper powder, further coating the copper powder.

[0039] In some embodiments, the concentration of AgNO3 in the silver source solution is 0.3 M~0.8 M, the mass ratio of gum arabic or gelatin to AgNO3 is (0.02~0.1):1; the concentration of the reducing agent solution is 0.3 M~0.8 M.

[0040] In some embodiments, in the replacement reaction step, the reaction temperature is 40°C~70°C, the mass ratio of the added amount of AgNO3 to the copper powder is (0.02~0.35):1, the dropping rate of the silver source solution is 1 mL / min~10 mL / min, the stirring rate is 200 rpm~600 rpm, the reaction time is 5 min~15 min, and the solution pH is adjusted to <1.5 after the reaction.

[0041] During the replacement reaction, adding the silver source solution to the copper powder suspension by dropwise addition can better control the morphology of the silver coating on the copper powder surface. Due to the low reduction potential of the copper powder, the copper powder and Ag + The replacement reaction occurs rapidly, Cu 2+ Copper hydroxide attachments are easily generated under higher pH conditions, which in turn affects subsequent redox deposition. At the end of the replacement reaction, the solution pH is adjusted to a strongly acidic environment to remove the copper hydroxide attached to the surface of the silver-coated copper powder precursor.

[0042] In some embodiments, in the redox reaction step, the molar ratio of the amount of reducing agent added to AgNO3 is (0.5~1.5):1; the droplet acceleration rate of the reducing agent solution is 1 mL / min~20 mL / min; the mass ratio of the amount of AgNO3 added to the copper powder is (0.08~1.30):1, the droplet acceleration rate of the silver source solution is 1 mL / min~20 mL / min, the stirring rate is 200 rpm~600 rpm, the reaction time is 25 min~35 min, and after solid-liquid separation, the solution is washed until the conductivity of the cleaning liquid is <15 μS / cm.

[0043] The synergistic effect of the drop order and drop rate of the reducing agent solution and the silver source solution will affect the Ag + The nucleation rate, morphology and structure of the silver-coated copper powder and the quality of the silver layer coating are controlled. Preferably, the reducing agent solution is added first and then the silver source solution is added, so that the silver-coated copper powder with different silver layer distribution structures, compact silver plating structure and better performance can be obtained.

[0044] In some embodiments, the coating agent includes one or more of ethylamine, stearic acid, palmitic acid, oleic acid, linoleic acid, and ricinoleic acid; the mass ratio of the coating agent to the silver-coated copper powder is (0.005~0.01):1, the coating temperature is 20℃~30℃, and the stirring rate is 200 rpm~600 rpm.

[0045] The coating agent modification treatment will improve the wettability and compatibility of silver-coated copper powder with the organic carrier, and improve the sintering activity of silver-coated copper powder in low-temperature slurry.

[0046] The following are specific embodiments, comparative examples and application examples. Example 1 Embodiment 1 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 5 wt% sodium hydroxide solution, performing ultrasonic stirring for 5 min, and centrifuging at a centrifugal speed of 500 rpm for 3 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 5 wt% hydrochloric acid solution, performing ultrasonic stirring for 5 min, and centrifuging at a centrifugal speed of 500 rpm for 3 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding ethylenediaminetetraacetic acid at a mass ratio of complexing agent to copper powder of 0.5:1, and stirring at a rate of 300 rpm to form a stable copper powder suspension; Step 3, continuously adding AgNO3 and gum arabic mixed solution to the copper powder suspension obtained in step 2 for replacement reaction, with a stirring rate of 200 rpm, a reaction temperature of 40°C, and a reaction time of 5 min. After the replacement reaction, concentrated HNO3 is used to adjust the solution pH to less than 1.5 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 in the mixture of AgNO3 and gum arabic was 0.3 M, the mass ratio of gum arabic to AgNO3 was 0.02:1; the mass ratio of the added amount of AgNO3 to the copper powder was 0.079:1, and the drop rate of the mixture of AgNO3 and gum arabic was 1 mL / min; Step 4, first add C6H8O6 solution to the silver-coated copper powder precursor suspension obtained in step 3, the concentration of C6H8O6 solution is 0.3 M, the drop rate of C6H8O6 solution is 8 mL / min, after stirring for 5 minutes, then add AgNO3 and gum arabic mixed solution for redox reaction, the stirring rate is 200 rpm, and the drop rate of AgNO3 and gum arabic mixed solution is 8 mL / min; after stirring for 25 minutes, settle, separate the solid and liquid, alternately dissolve the precipitate in anhydrous ethanol and deionized water, perform ultrasonic cleaning, centrifuge until the conductivity of the cleaning solution is less than 15 μS / cm, and dry to obtain silver-coated copper powder; Among them, the molar ratio of the added amount of C6H8O6 to AgNO3 is 0.6:1; the mass ratio of the added amount of AgNO3 to copper powder is 0.315:1.

[0047] Example 2 Embodiment 2 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 20 wt% Na3PO4 solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 1000 rpm for 6 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 20 wt% sulfuric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 1000 rpm for 6 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding citric acid at a mass ratio of complexing agent to copper powder of 1.5:1, and stirring at a rate of 300 rpm to form a stable copper powder suspension; Step 3, continuously adding AgNO3 solution to the copper powder suspension obtained in step 2 for replacement reaction, with a stirring rate of 600 rpm, a reaction temperature of 70°C, and a reaction time of 15 min. After the replacement reaction, concentrated HNO3 is used to adjust the solution pH to less than 1.5 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 was 0.3 M; the mass ratio of the added amount of AgNO3 to the copper powder was 0.079:1, and the drop rate of the AgNO3 solution was 2 mL / min; Step 4: first add C6H 12 O6 solution, C6H 12 The concentration of O6 solution is 0.8 M, C6H 12 The O6 solution was added at a rate of 12 mL / min, and after stirring for 5 min, the AgNO3 solution was added dropwise for redox reaction, and the stirring rate was 600 rpm. The AgNO3 solution was added at a rate of 12 mL / min. After stirring for 35 min, the solution was allowed to settle, and the solid and liquid were separated. The precipitate was alternately dissolved in anhydrous ethanol and deionized water, and ultrasonically cleaned. The solution was centrifuged until the conductivity of the cleaning solution was less than 15 μS / cm, and dried to obtain silver-coated copper powder. Among them, the molar ratio of the added amount of C6H8O6 to AgNO3 is 0.6:1; the mass ratio of the added amount of AgNO3 to copper powder is 0.315:1.

[0048] Example 3 Embodiment 3 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding tartaric acid at a mass ratio of complexing agent to copper powder of 1:1, and stirring at a rate of 300 rpm to form a stable copper powder suspension; Step 3, continuously adding AgNO3 and gelatin mixed solution to the copper powder suspension obtained in step 2 for replacement reaction, with a stirring rate of 400 rpm, a reaction temperature of 50°C, and a reaction time of 10 min. After the replacement reaction, concentrated HNO3 is used to adjust the solution pH to less than 1.5 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 in the mixed solution of AgNO3 and gelatin was 0.5 M, the mass ratio of gelatin to AgNO3 was 0.1:1; the mass ratio of the added amount of AgNO3 to the copper powder was 0.079:1, and the drop rate of the mixed solution of AgNO3 and gelatin was 10 mL / min. Step 4, first add FeSO4 solution to the silver-coated copper powder precursor suspension obtained in step 3, the concentration of FeSO4 solution is 0.6 M, the dropping rate of FeSO4 solution is 10 mL / min, after stirring for 5 minutes, then add AgNO3 and gelatin mixed solution to carry out redox reaction, the stirring rate is 400 rpm, and the dropping rate of AgNO3 and gelatin mixed solution is 10 mL / min; after stirring for 30 minutes, settle, separate the solid and liquid, alternately dissolve the precipitate in anhydrous ethanol and deionized water, perform ultrasonic cleaning, centrifuge until the conductivity of the cleaning solution is less than 15 μS / cm, and dry to obtain silver-coated copper powder; Among them, the amount of FeSO4 added to AgNO3 is 1.2:1; the mass ratio of AgNO3 added to copper powder is 0.315:1.

[0049] Example 4 Embodiment 4 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding a mixture of ethylenediaminetetraacetic acid and citric acid at a mass ratio of 1:1 between the complexing agent and the copper powder, and stirring at a rate of 300 rpm to form a stable copper powder suspension; The mass ratio of ethylenediaminetetraacetic acid to citric acid is 0.5:1; Step 3, continuously adding AgNO3 and gum arabic mixed solution to the copper powder suspension obtained in step 2 for replacement reaction, with a stirring rate of 400 rpm, a reaction temperature of 50°C, and a reaction time of 10 min. After the replacement reaction, concentrated HNO3 is used to adjust the solution pH to less than 1.5 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 in the mixture of AgNO3 and gum arabic was 0.5 M, the mass ratio of gum arabic to AgNO3 was 0.1:1; the mass ratio of the amount of AgNO3 added to the copper powder was 0.079:1, and the drop rate of the mixture of AgNO3 and gum arabic was 2 mL / min; Step 4, first add C6H8O6 solution to the silver-coated copper powder precursor suspension obtained in step 3, the concentration of C6H8O6 solution is 0.6 M, the drop rate of C6H8O6 solution is 10 mL / min, after stirring for 5 min, then add AgNO3 and gum arabic mixed solution for redox reaction, the stirring rate is 400 rpm, and the drop rate of AgNO3 and gum arabic mixed solution is 10 mL / min; after stirring for 30 min, settle, separate the solid and liquid, alternately dissolve the precipitate in anhydrous ethanol and deionized water, perform ultrasonic cleaning, centrifuge until the conductivity of the cleaning solution is less than 15 μS / cm, and dry to obtain silver-coated copper powder; Among them, the mass ratio of C6H8O6 addition to AgNO3 is 0.6:1; the mass ratio of AgNO3 addition to copper powder is 0.315:1; Step 5, coating the silver-coated copper powder obtained in step 4 with oleic acid, the mass ratio of oleic acid to silver-coated copper powder is 0.005:1, the coating temperature is 25°C, the stirring rate is 300 rpm, and after stirring, it is placed in anhydrous ethanol solution for washing, sedimentation, solid-liquid separation, and drying.

[0050] The SEM image, thermogravimetric analysis and XRD image of the silver-coated copper powder provided in Example 4 are as follows: Figures 1 to 3 shown.

[0051] Example 5 Example 5 provides a method for preparing silver-coated copper powder, which is different from Example 4 in that, in step 5 of Example 5, the coating agent is a mixture of oleic acid and ethylamine, the mixing ratio of oleic acid and ethylamine is 0.5:1, the mass ratio of the added amount of the coating agent to the silver-coated copper powder is 0.01:1, the coating temperature is 20°C, and the stirring rate is 200 rpm.

[0052] Example 6 Example 6 provides a method for preparing silver-coated copper powder, which is different from Example 4 in that, in step 5 of Example 6, the coating agent is a mixture of oleic acid and palmitic acid, the mixing ratio of oleic acid and palmitic acid is 0.5:1, the mass ratio of the added amount of the coating agent to the silver-coated copper powder is 0.008:1, the coating temperature is 30°C, and the stirring rate is 600 rpm.

[0053] Comparative Example Comparative Example 1 Comparative Example 1 provides a method for preparing silver-coated copper powder. The difference from Example 5 is that Comparative Example 1 does not include step 4 and does not perform an oxidation-reduction reaction, which is as follows: Comparative Example 1 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding a mixture of ethylenediaminetetraacetic acid and citric acid at a mass ratio of 1:1 between the complexing agent and the copper powder, and stirring at a rate of 300 rpm to form a stable copper powder suspension; The mass ratio of ethylenediaminetetraacetic acid to citric acid is 0.5:1; Step 3, continuously adding AgNO3 and gum arabic mixed solution to the copper powder suspension obtained in step 2 for replacement reaction, the stirring rate is 400 rpm, the reaction temperature is 50°C, the reaction time is 10 min, after the replacement reaction is completed, the solution pH is adjusted to less than 1.5 with concentrated HNO3 to obtain a silver-coated copper powder precursor suspension, sedimentation, solid-liquid separation, the precipitate is alternately dissolved in anhydrous ethanol and deionized water, ultrasonic cleaning is performed, centrifugation is performed until the conductivity of the cleaning solution is less than 15 μS / cm, and drying is performed to obtain silver-coated copper powder; The concentration of AgNO3 in the mixture of AgNO3 and gum arabic was 0.5 M, the mass ratio of gum arabic to AgNO3 was 0.1:1; the mass ratio of the amount of AgNO3 added to the copper powder was 0.079:1, and the drop rate of the mixture of AgNO3 and gum arabic was 2 mL / min; Step 4, coating the silver-coated copper powder obtained in step 3 with oleic acid, the mass ratio of oleic acid to silver-coated copper powder is 0.005:1, the coating temperature is 25°C, the stirring rate is 300 rpm, and after stirring, it is placed in anhydrous ethanol solution for washing, sedimentation, solid-liquid separation, and drying.

[0054] Comparative Example 2 Comparative Example 2 provides a method for preparing silver-coated copper powder, which is different from Example 4 in that, in step 4 of Comparative Example 2, a mixed solution of AgNO3 and gum arabic is first added dropwise, and then a C6H8O6 solution is added dropwise. The details are as follows: Comparative Example 2 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding a mixture of ethylenediaminetetraacetic acid and citric acid at a mass ratio of 1:1 between the complexing agent and the copper powder, and stirring at a rate of 300 rpm to form a stable copper powder suspension; The mass ratio of ethylenediaminetetraacetic acid to citric acid is 0.5:1; Step 3, continuously adding AgNO3 and gum arabic mixed solution to the copper powder suspension obtained in step 2 for replacement reaction, with a stirring rate of 400 rpm, a reaction temperature of 50°C, and a reaction time of 10 min. After the replacement reaction, concentrated HNO3 is used to adjust the solution pH to less than 1.5 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 in the mixture of AgNO3 and gum arabic was 0.5 M, the mass ratio of gum arabic to AgNO3 was 0.1:1; the mass ratio of the amount of AgNO3 added to the copper powder was 0.079:1, and the drop rate of the mixture of AgNO3 and gum arabic was 2 mL / min; Step 4, first add a mixed solution of AgNO3 and gum arabic to the silver-coated copper powder precursor suspension obtained in step 3, the mixed solution of AgNO3 and gum arabic is added at a dropping rate of 10 mL / min, stirred for 5 min, and then C6H8O6 is added for redox reaction, the concentration of C6H8O6 solution is 0.6 M, the dropping rate of C6H8O6 solution is 10 mL / min, the stirring rate is 400 rpm, and the precipitation is carried out after stirring for 30 min, the solid-liquid separation, the precipitate is alternately dissolved in anhydrous ethanol and deionized water, ultrasonically cleaned, centrifuged until the conductivity of the cleaning solution is less than 15 μS / cm, and dried to obtain silver-coated copper powder; Among them, the mass ratio of C6H8O6 addition to AgNO3 is 0.6:1; the mass ratio of AgNO3 addition to copper powder is 0.315:1; Step 5, coating the silver-coated copper powder obtained in step 4 with oleic acid, the mass ratio of oleic acid to silver-coated copper powder is 0.005:1, the coating temperature is 25°C, the stirring rate is 300 rpm, and after stirring, it is placed in anhydrous ethanol solution for washing, sedimentation, solid-liquid separation, and drying.

[0055] Comparative Example 3 Comparative Example 3 provides a method for preparing silver-coated copper powder, which is different from Example 4 in that, in step 4 of Comparative Example 3, during the oxidation-reduction reaction, a C6H8O6 solution, AgNO3 and a mixture of gum arabic are added dropwise at the same time. The details are as follows: Comparative Example 3 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding a mixture of ethylenediaminetetraacetic acid and citric acid at a mass ratio of 1:1 between the complexing agent and the copper powder, and stirring at a rate of 300 rpm to form a stable copper powder suspension; The mass ratio of ethylenediaminetetraacetic acid to citric acid is 0.5:1; Step 3, continuously adding AgNO3 and gum arabic mixed solution to the copper powder suspension obtained in step 2 for replacement reaction, with a stirring rate of 400 rpm, a reaction temperature of 50°C, and a reaction time of 10 min. After the replacement reaction, concentrated HNO3 is used to adjust the solution pH to less than 1.5 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 in the mixture of AgNO3 and gum arabic was 0.5 M, the mass ratio of gum arabic to AgNO3 was 0.1:1; the mass ratio of the amount of AgNO3 added to the copper powder was 0.079:1, and the drop rate of the mixture of AgNO3 and gum arabic was 2 mL / min; Step 4, adding C6H8O6 solution and AgNO3 and gum arabic mixture to the silver-coated copper powder precursor suspension obtained in step 3 at the same time to carry out redox reaction, the concentration of C6H8O6 solution is 0.6 M, the dropping rate of C6H8O6 solution is 10 mL / min, the dropping rate of AgNO3 and gum arabic mixture is 10 mL / min, the stirring rate is 400 rpm, and the precipitation is carried out after stirring for 30 min, the solid-liquid separation is carried out, the precipitate is alternately dissolved in anhydrous ethanol and deionized water, ultrasonic cleaning is carried out, centrifugation is carried out until the conductivity of the cleaning solution is less than 15 μS / cm, and drying is carried out to obtain silver-coated copper powder; Among them, the mass ratio of C6H8O6 addition to AgNO3 is 0.6:1; the mass ratio of AgNO3 addition to copper powder is 0.315:1; Step 5, coating the silver-coated copper powder obtained in step 4 with oleic acid, the mass ratio of oleic acid to silver-coated copper powder is 0.005:1, the coating temperature is 25°C, the stirring rate is 300 rpm, and after stirring, it is placed in anhydrous ethanol solution for washing, sedimentation, solid-liquid separation, and drying.

[0056] Comparative Example 4 Comparative Example 4 provides a method for preparing silver-coated copper powder, which differs from Example 5 in that, in step 4, the droplet acceleration rate of the AgNO3 and gum arabic mixture is 0.5 mL / min.

[0057] Comparative Example 5 Comparative Example 5 provides a method for preparing silver-coated copper powder, which differs from Example 5 in that, in step 4, the droplet acceleration rate of the AgNO3 and gum arabic mixture is 25 mL / min.

[0058] Comparative Example 6 Comparative Example 6 provides a method for preparing silver-coated copper powder. The difference from Example 5 is that the replacement reaction in step 3 is not performed in Comparative Example 6. The details are as follows: Comparative Example 6 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, adding a mixture of ethylenediaminetetraacetic acid and citric acid at a mass ratio of 1:1 between the complexing agent and the copper powder, and stirring at a rate of 300 rpm to form a stable copper powder suspension; The mass ratio of ethylenediaminetetraacetic acid to citric acid is 0.5:1; Step 3, first add C6H8O6 solution to the copper powder suspension obtained in step 2, the concentration of C6H8O6 solution is 0.6 M, the drop rate of C6H8O6 solution is 10 mL / min, after stirring for 5 minutes, then add AgNO3 and gum arabic mixed solution for redox reaction, the stirring rate is 400 rpm, and the drop rate of AgNO3 and gum arabic mixed solution is 10 mL / min; after stirring for 30 minutes, settle, separate the solid and liquid, alternately dissolve the precipitate in anhydrous ethanol and deionized water, perform ultrasonic cleaning, centrifuge until the conductivity of the cleaning solution is less than 15 μS / cm, and dry to obtain silver-coated copper powder; The concentration of AgNO3 in the mixed solution of AgNO3 and gum arabic was 0.5 M, the mass ratio of gum arabic to AgNO3 was 0.1:1; the molar ratio of the amount of C6H8O6 added to AgNO3 was 0.6:1; the mass ratio of the amount of AgNO3 added to copper powder was 0.315:1; Step 4, coating the silver-coated copper powder obtained in step 3 with oleic acid, the mass ratio of oleic acid to silver-coated copper powder is 0.005:1, the coating temperature is 25°C, the stirring rate is 300 rpm, and after stirring, it is placed in anhydrous ethanol solution for washing, sedimentation, solid-liquid separation, and drying.

[0059] Comparative Example 7 Comparative Example 7 provides a method for preparing silver-coated copper powder. The difference from Example 5 is that step 2 is not performed in Comparative Example 7. The details are as follows: Comparative Example 7 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1, dissolving the copper powder after ultrasonic cleaning in a 10 wt% sodium hydroxide solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to remove grease on the surface of the copper powder; then dissolving the degreased copper powder in a 10 wt% nitric acid solution, performing ultrasonic stirring for 10 min, and centrifuging at a centrifugal speed of 800 rpm for 5 times to obtain activated copper powder; Step 2, dissolving the activated copper powder in deionized water, stirring at a rate of 300 rpm, continuously dropping a mixture of AgNO3 and gum arabic for replacement reaction, stirring at a rate of 400 rpm, the reaction temperature is 50°C, the reaction time is 10 min, and after the replacement reaction is completed, the pH of the solution is adjusted to less than 1.5 with concentrated HNO3 to obtain a silver-coated copper powder precursor suspension; The concentration of AgNO3 in the mixture of AgNO3 and gum arabic was 0.5 M, the mass ratio of gum arabic to AgNO3 was 0.1:1; the mass ratio of the amount of AgNO3 added to the copper powder was 0.079:1, and the drop rate of the mixture of AgNO3 and gum arabic was 2 mL / min; Step 3, first add C6H8O6 solution to the silver-coated copper powder precursor suspension obtained in step 2, the concentration of C6H8O6 solution is 0.6 M, the drop rate of C6H8O6 solution is 10 mL / min, after stirring for 5 minutes, then add AgNO3 and gum arabic mixed solution for redox reaction, the stirring rate is 400 rpm, and the drop rate of AgNO3 and gum arabic mixed solution is 10 mL / min; after stirring for 30 minutes, settle, separate the solid and liquid, alternately dissolve the precipitate in anhydrous ethanol and deionized water, perform ultrasonic cleaning, centrifuge until the conductivity of the cleaning solution is less than 15 μS / cm, and dry to obtain silver-coated copper powder; Among them, the mass ratio of C6H8O6 addition to AgNO3 is 0.6:1; the mass ratio of AgNO3 addition to copper powder is 0.315:1; Step 4, coating the silver-coated copper powder obtained in step 3 with oleic acid, the mass ratio of oleic acid to silver-coated copper powder is 0.005:1, the coating temperature is 25°C, the stirring rate is 300 rpm, and after stirring, it is placed in anhydrous ethanol solution for washing, sedimentation, solid-liquid separation, and drying.

[0060] Comparative Example 8 Comparative Example 8 provides a method for preparing silver-coated copper powder, specifically using the silver-coated copper powder and its preparation method and electronic paste disclosed in Application No. 2020101608289, as follows: Comparative Example 8 provides a method for preparing silver-coated copper powder, comprising the following steps: Step 1: First, the purchased copper powder is ultrasonically cleaned with octylphenol polyoxyethylene ether-10 for 5-10 minutes, and then ultrasonically cleaned three times with deionized water to remove octylphenol polyoxyethylene ether-10; then, the micron copper powder is ultrasonically cleaned with 5% dilute sulfuric acid for 5-10 minutes to remove the oxide film on its surface, and then ultrasonically cleaned with deionized water three times until the washing solution is neutral, and the obtained copper powder is ready for use.

[0061] Step 2, take 4.5 g of silver nitrate and dissolve it in 100 mL of aqueous solution. While stirring, add 20% ammonia water dropwise into the silver nitrate solution until the precipitate just disappears. Set aside.

[0062] Step 3, take 40 mL of the prepared silver ammonia solution, add 8 g of pretreated copper powder, and then add 100 mL of 0.05 mol / L glucose solution. After sufficient stirring, add 20 mL of 20% ammonia water, the solution quickly turns from transparent to blue, and the copper powder dispersed in the solution changes from bright red brown to light gray. After reacting for 5 minutes, separate the solid and liquid with a Buchner funnel, and wash the solid repeatedly with deionized water three times to obtain the first silver-plated intermediate product.

[0063] Step 4, add the intermediate product obtained by the first silver plating to 200 mL of 0.5 g / L polyvinyl pyrrolidone solution, and mix thoroughly for 5 min under mechanical stirring at 400 r / min. Then, at 40 ° C, add the remaining silver ammonia solution diluted to 120 mL and 150 mL of 0.05 mol / L glucose solution at a rate of 60 mL / min. After the addition is completed, continue the reaction for 1 h. After the reaction is completed, wash it repeatedly with deionized water and anhydrous ethanol three times, and dry it at 60 ° C for 4 h to obtain a core-shell structured silver-coated copper powder.

[0064] Application Examples This application example provides a low-temperature conductive paste prepared from the silver-coated copper powder of Examples 1-6 and Comparative Examples 1-8. The low-temperature conductive paste components include 40% of the silver-coated copper powder provided by any of Examples 1-6 and Comparative Examples 1-8, 52% of nanopowder, 2.5% of resin, 4.1% of solvent, 1.36% of isocyanate curing agent, and 0.04% of dispersant.

[0065] This application example also provides a method for preparing a low-temperature conductive paste, comprising the following steps: The mixture of the above components is ground through a three-roll mill at a roller spacing of 5-120 μm to reduce fineness and improve dispersibility to obtain a uniformly dispersed low-temperature slurry; The low-temperature slurry was screen-printed to form a rectangular electrode with a length of 3 cm and a width of 0.8 cm on a silicon wafer, and then cured and sintered at a curing temperature of 200 °C and a curing time of 30 min to obtain a low-temperature conductive slurry.

[0066] Performance Testing Test Method 1. Determination of silver content The actual silver content of silver-coated copper powder was studied by chemical precipitation method. The main method is to weigh m1 mass of silver-coated copper powder, dissolve it in concentrated nitric acid and dilute it, then use a slightly excessive amount of NaCl dilute solution to precipitate it, and after the precipitation is complete, dilute it with water, filter it, wash it, and after it is fully dried, use an electronic balance to weigh the precipitate mass m2, the actual silver content W Ag The calculation method of is as follows:

[0067] 2. Determination of tap density First, weigh a certain weight of silver-coated copper powder and put it all into the tap density measuring cylinder. Then fix the measuring cylinder containing the powder on the instrument and vibrate it. Set the vibration number to 3000 times and the frequency to 250 times / min. After the vibration, visually measure the volume according to the height of the powder surface, and then calculate the tap density. The calculation formula is as follows:

[0068] Take 3 samples from the same batch, measure them in parallel, record the readings, and take the average value as the measurement result.

[0069] 3. Antioxidant test ① Determination of initial oxidation temperature: The determination of the onset oxidation temperature can be carried out by thermogravimetric analysis (TGA), which is determined by heating the sample and monitoring its mass change. In the TGA experiment, when the sample is heated to a high temperature, an oxidation reaction occurs and the mass of the sample will gradually increase. By analyzing the mass change curve, the onset oxidation temperature of the powder can be determined.

[0070] ②600℃ oxidation weight gain: The determination of 600 ℃ oxidation weight gain can be carried out by thermogravimetric analysis (TGA), which determines the final oxidation weight gain by heating the sample and monitoring its mass change. In a TGA experiment, when the sample is heated to a high temperature, an oxidation reaction occurs, and the mass of the sample will gradually increase and tend to stabilize.

[0071] 4. Electrical performance test of low temperature slurry The silver-coated copper powder is compounded with the silver powder to prepare a low-temperature slurry; The low temperature slurry was tested for resistance, and the average resistance value was taken after five tests; The cross-sectional area of ​​the electrode was measured by a step profiler for low-temperature slurry. The area size at different positions was tested and the average value was taken after five tests. The paste resistivity of low temperature paste is calculated by line resistance × cross-sectional area / electrode length.

[0072] The silver-coated copper powders prepared by the silver-coated copper powder preparation methods of Examples 1-6 and Comparative Examples 1-8 were tested by the above-mentioned test method. The data of silver content, tap density, initial oxidation temperature and sintering activity are shown in Table 1 below.

[0073] Table 1 Performance test of silver-coated copper powder Silver content / % <![CDATA[Tap density / (g / cm 3 )]]> Initial oxidation temperature / (℃) 600℃ oxidation weight gain / (%) Example 1 26.6 3.98 265.53 20.1 Example 2 22.5 4.04 266.45 18.4 Example 3 23.8 3.86 284.23 19.3 Example 4 28.3 4.07 295.84 12.4 Example 5 27.9 4.12 294.23 12.7 Example 6 27.6 4.05 293.56 13.1 Comparative Example 1 22.5 2.85 205.84 16.8 Comparative Example 2 24.5 3.65 248.85 17.1 Comparative Example 3 26.6 3.78 263.65 17.2 Comparative Example 4 24.5 3.59 270.92 19.7 Comparative Example 5 26.2 3.66 252.75 18.9 Comparative Example 6 21.6 2.86 228.50 16.9 Comparative Example 7 18.3 4.23 235.56 19.3 Comparative Example 8 19.5 3.77 240.56 21.1 The data comparison in Table 1 shows the difference in comprehensive performance of silver-coated copper powder between Examples 1-6 and Comparative Examples 1-8, especially in key indicators such as tap density, initial oxidation temperature and 600° C. oxidation weight gain. These indicators together reflect the performance of silver-coated copper powder in conductivity, stability and oxidation resistance.

[0074] It can be seen from the data that Examples 1-6 have excellent overall performance, especially Example 4, whose various performance indicators have reached the best state. In addition, its silver content is 28.3% and its tap density is 4.07 g / cm³, indicating that the silver layer is evenly and densely covered, and the powder structure is compact, which can effectively improve the conductivity. More importantly, the initial oxidation temperature of Example 4 is as high as 295.84 ℃, and the oxidation weight gain at 600 ℃ is only 12.4%, which shows that the silver-coated copper powder has strong antioxidant ability at high temperature and can maintain stable performance in high temperature applications.

[0075] In contrast, the performance of Comparative Examples 1-8 is significantly inferior, especially in terms of silver content and antioxidant performance. For example, the initial oxidation temperature of Comparative Example 1 is 205.84 ° C, and the oxidation weight gain at 600 ° C reaches 16.8%, which indicates that its silver layer is unevenly covered, the structure is loose, it is easy to oxidize under high temperature environment, and the overall stability is poor. The tap density of these comparative examples is low and the weight loss rate is high, which further reflects that its silver coating effect is poor, and its conductive performance and long-term stability are far inferior to those of the embodiments.

[0076] In summary, the data in Table 1 clearly demonstrates how the optimized preparation process can significantly improve the performance of silver-coated copper powder. Example 4 represents the best effect of the method of the present invention, showing excellent conductivity and antioxidant properties, and is suitable for application scenarios with high requirements for material stability. Due to process defects, the comparative samples failed to achieve the same performance improvement, limiting their effectiveness in practical applications. Overall, the silver-coated copper powder in the examples shows significant advantages in conductivity, structural stability and high-temperature antioxidant properties, laying a solid foundation for its application in high-end electronic materials.

[0077] The silver-coated copper powders provided in Examples 1-6 and Comparative Examples 1-8 were respectively made into low-temperature conductive slurries through application examples, and the electrochemical properties were measured by the test method, as shown in Table 2.

[0078] Table 2 Electrochemical performance test of low temperature conductive paste in application example

[0079] The data comparison in Table 2 shows the difference in electrochemical performance between Examples 1-6 and Comparative Examples 1-8 in the low-temperature conductive slurry of silver-coated copper powder. These data show that different preparation methods have a significant impact on the conductivity and material properties of silver-coated copper powder.

Claims

1. A method for preparing silver-coated copper powder, characterized in that: The following steps are involved: The copper powder surface activated by the acid-base solution and the complexing agent are dissolved in water to obtain a copper powder suspension; Adding a silver source solution dropwise to the copper powder suspension to carry out a replacement reaction, and adjusting the pH of the solution after the reaction to obtain a silver-coated copper powder precursor suspension; A reducing agent solution is firstly added dropwise to the silver-coated copper powder precursor suspension, and then a silver source solution is added dropwise to carry out an oxidation-reduction reaction, and the solid-liquid separation, washing and drying are performed to obtain the silver-coated copper powder.

2. The method for preparing a silver-coated copper powder according to claim 1, characterized in that: The method also includes the following steps: coating the silver-coated copper powder with a coating agent, solid-liquid separation, washing, and drying.

3. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The acid-base solution includes an acidic solution and an alkaline solution; the acidic solution includes one or more of HCl solution, HNO3 solution, H2SO4 solution, and H2O2 solution, and the concentration of the acidic solution is 5 wt% to 20 wt%; The alkaline solution includes one or more of NaOH solution, Na2CO3 solution, and Na3PO4 solution, and the concentration of the alkaline solution is 5 wt%~20 wt%.

4. The method for preparing a silver-coated copper powder according to claim 1, characterized in that: The complexing agent includes one or more of ethylenediaminetetraacetic acid, tartaric acid, and citric acid; the mass ratio of the complexing agent to the copper powder is (0.5-1.5):

1.

5. The method for preparing silver-coated copper powder according to claim 1, characterized in that: The silver source solution includes one of AgNO3, a mixture of AgNO3 and gum arabic, and a mixture of AgNO3 and gelatin; The reducing agent solution is C6H8O6 solution, FeSO4 solution, C6H 12 O6 solution or more.

6. The method for preparing silver-coated copper powder according to claim 5, characterized in that: The AgNO3 concentration in the silver source solution is 0.3 M~0.8 M, the mass ratio of gum arabic or gelatin to AgNO3 is (0.02~0.1):1; the concentration of the reducing agent solution is 0.3 M~0.8 M.

7. The method for preparing silver-coated copper powder according to claim 6, characterized in that: In the replacement reaction step, the reaction temperature is 40°C~70°C, the mass ratio of the added amount of AgNO3 to the copper powder is (0.02~0.35):1, the dropping rate of the silver source solution is 1 mL / min~10 mL / min, the stirring rate is 200 rpm~600 rpm, the reaction time is 5 min~15 min, and the solution pH is adjusted to <1.5 after the reaction.

8. The method for preparing silver-coated copper powder according to claim 7, characterized in that: In the oxidation-reduction reaction step, the molar ratio of the amount of reducing agent added to AgNO3 is (0.5~1.5):1; the drop rate of the reducing agent solution is 1mL / min~20 mL / min; the mass ratio of the amount of AgNO3 added to the copper powder is (0.08~1.28):1, the drop rate of the silver source solution is 1 mL / min~20 mL / min, the stirring rate is 200 rpm~600 rpm, the reaction time is 25 min~35 min, and after solid-liquid separation, washing is performed until the conductivity of the cleaning liquid is <15 μS / cm.

9. The method for preparing silver-coated copper powder according to claim 2, characterized in that: The coating agent includes one or more of ethylamine, stearic acid, palmitic acid, oleic acid, linoleic acid, and ricinoleic acid; The mass ratio of the coating agent to the silver-coated copper powder is (0.005-0.01):1, the coating temperature is 20°C-30°C, and the stirring rate is 200 rpm-600 rpm.

10. A silver-coated copper powder, characterized in that: The silver-coated copper powder is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of smooth and compact silver-coated copper powder

    CN120115713A

  • Silver-coated copper powder and preparation method thereof

    CN120961913A

  • Method for preparing silver-coated copper powder by using retired photovoltaic cell recycled waste liquid

    CN122164897A

  • Method for preparing silver-coated copper powder by using waste liquid recovered from retired photovoltaic cell pieces

    CN122164897B

  • Preparation process of silver-coated copper powder

    CN122279554A